1967
DOI: 10.1093/bja/39.10.806
|View full text |Cite
|
Sign up to set email alerts
|

Protective Hypothermia for Cancer Chemotherapy

Abstract: Experience is reported of the use of immersion hypothermia on twenty-one occasions in seventeen patients in whom ethoglucid was injected by the intra-arterial route for the treatment of advanced cancer of the head and neck. The main hazards were found to be arterial hypotension occurring during the procedure and postoperative regional oedema leading to respiratory obstruction for which tracheostomy was required on eight occasions. The fall in white blood cell count was appreciably less than that reported after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In a study by Fay Temple in 1940, hypothermia therapy resulted in a remarkable recovery from breast carcinoma (30). Since then, various studies concluded that hypothermia suppressed cancer cell proliferation, adhesion, and metastasis to neighboring cells (31)(32)(33)(34). In addition, blood regulation is greatly influenced by hypothermia.…”
mentioning
confidence: 99%
“…In a study by Fay Temple in 1940, hypothermia therapy resulted in a remarkable recovery from breast carcinoma (30). Since then, various studies concluded that hypothermia suppressed cancer cell proliferation, adhesion, and metastasis to neighboring cells (31)(32)(33)(34). In addition, blood regulation is greatly influenced by hypothermia.…”
mentioning
confidence: 99%
“…Body temperature influences the sensitivity of tissues and organisms to ionising radiation (1 -4) and presumably to chemotherapy as well (5)(6)(7). Hyperthermia is in clinical use (8) but for whole-body hyperthermia the relation between tolerability and temperature increase and duration is steep, limiting its usefulness in disseminated malignancy.…”
mentioning
confidence: 99%
“…9, 10). Few studies have been published on the relative cytotoxic effect of chemicals or irradiation on neoplastic and normal tissues at temperatures below that of the normal body (5,11,12). It was therefore decided to test various clinically used cytotoxic drugs at normal and subnormal temperatures, being feasible also for humans (cf.…”
mentioning
confidence: 99%